Lietuvos moterų visuomeninis judėjimas ir kova už politinį lygiateisiškumą XX amžiaus pradžioje - Jurėnienė, Virginija (Lietuvos istorijos studijos, 2003)
Lithuanian women started to organize themselves in 1905. In October 1905, a women amalgamation was established. Its aim was to join women into the movement for their political and civil rights. In 1907, in Kaunas, the first women assembly was organized. Women of different social status attended the assembly. Among them were the writers Julija Žemaitė-Žymantienė, Gabrielė Petkevičaitė-Bitė, Liudvika Didžiulienė, Ona Pleirytė-Puidienė, Marija Pečkauskaitė-Šatrijos Ragana, Sofija Ivanauskaitė-Pšibiliauskienė-Lazdynų Pelėda, the socially active women Felicija Bortkevičienė, servants, women workers, and peasants. Most of the assembly members were country women. They spoke about the wrongs that had been done to them. They wanted to get some advice and ways to solve their problems. The political parties, i.e., Social Democrats, Democrats, and Christian Democrats, wanted to gain influence on the women’s movement. Only the Christian Democrats succeeded in this. This party organized the first women’s assembly and the Christian women’s organization. As a result, the women’s movement split into two organizations: Christian women and laywomen. The Lithuanian Christian women’s organization was established in March 1908. The public women’s organization wasn’t formally established because the Russian officials did not issue a license for their activity.